Islamic Economic Politics in Alleviating Poverty in Indonesia - Azwar Cholili; Imam Muslih; Anisatul Maghfiroh; Muh. Syaukin Muttaqin; Ali Arifin (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
Poverty alleviation has been a major problem in Indonesia for a long time. This happened because the number of poverty increased by more than a quarter after the crisis that occurred in 1998 and 2008. Meanwhile, Indonesia has experienced extraordinary changes, namely transformation in the social and political fields in line with the development of democracy, with the decentralization of government, and there is also greater transparency in the field of financial management which is much improved compared to what we had in the past. The government's commitment to poverty alleviation has been outlined in the 2005-2009 Medium Term Development Plan (RPJM) which is based on the National Poverty Reduction Strategy (SNPK). However, the poverty rate is still high regardless of any factor. This article focuses on discussing poverty which continues to reduce various poverty alleviation programs that have been launched by the government. The author has analyzed the phenomenon of absolute poverty based on political views, where these variables are related to economic growth since basic economic activity can influence poverty levels